2016
DOI: 10.1002/smll.201601307
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Solvation Effects at a Liquid/Nanoparticle Interface by Ab Initio Molecular Dynamics: Pt201 Immersed in Water

Abstract: Abstract. Solvation can substantially modify the adsorption properties of heterogeneous catalysts. Although essential for achieving realistic theoretical models, assessing such solvent effects over nanoparticles is challenging from a computational standpoint due to the complexity of those liquid/metal interfaces. We investigate this effect by ab initio moleculardynamics simulations at 350 K of a large platinum nanoparticle immersed in liquid water. The first solvation layer contains twice as much physisorbed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 72 publications
2
36
1
Order By: Relevance
“…In computational electrocatalysis adsorbate‐solvent and adsorbate‐electrolyte interactions at the interface can be evaluated implicitly (where the solvent is modelled as a continuum with certain dielectric constant), explicitly, or through combinations of the two . Furthermore, efforts have been devoted to determine the minimal number of explicit water molecules needed to stabilize a given adsorbate .…”
Section: Computational Detailsmentioning
confidence: 99%
“…In computational electrocatalysis adsorbate‐solvent and adsorbate‐electrolyte interactions at the interface can be evaluated implicitly (where the solvent is modelled as a continuum with certain dielectric constant), explicitly, or through combinations of the two . Furthermore, efforts have been devoted to determine the minimal number of explicit water molecules needed to stabilize a given adsorbate .…”
Section: Computational Detailsmentioning
confidence: 99%
“…6,7 Experimentally and computationally it has been shown that, depending on the catalyst, water can play a non-innocent role during heterogeneous catalysis. [8][9][10][11] However, the computational approaches that are well suited to describe reactions at the solid-gas-phase interface are 2 not necessarily suitable to describe the solid-liquid interface: the amorphous character of these interfaces make static computations questionable, while ab initio molecular dynamics (AIMD) simulations are too costly to be routinely applied [12][13][14][15][16] and also the cost of adaptive QM/MM is prohibitive for metal surfaces. 17,18 Therefore, approximate methods have been developed aiming at representing the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent effects may be accounted for using implicit models, 6,[9][10] though it is generally desirable to include them explicitly, especially when strong solvent-adsorbate interactions such as H-bonds are present. 11 Embedded methods exist with explicit solvent molecules in the first solvation shell and an implicit medium beyond, but the results need careful benchmark. [12][13][14] All those models capitalize on the conclusions and advances on the solvation of chemical species, mostly ions, in solution, which is a well-established field of research.…”
mentioning
confidence: 99%
“…Hence, one can safely add these solvation energies to In case not only shifts to the energies in vacuum are needed and explicit solvent descriptions are required, micro-solvation is also helpful: for instance, Pt 201 has a diameter of ~1.7 nm and AIMD simulations at 350 K found that ~1/3 of the 122 surface atoms are covered by water. 11 Thus, the high computational cost required to dynamically describe water/metal interfaces at finite temperature makes our static approach useful, as merely three water molecules and no implicit environment are needed.…”
mentioning
confidence: 99%